Causal roles of educational duration in bone mineral density and risk factors for osteoporosis: a Mendelian randomization study - Yujun Qin; Xia Yang; Zong Ning (BMC Musculoskeletal Disorders, 2024)
Abstract Background Educational duration might play a vital role in preventing the occurrence and development of osteoporosis(OP). Purpose To assess the causal effect of educational duration on bone mineral density(BMD) and risk factors for OP by Mendelian randomization(MR) study. Methods The causal relationship was analyzed using data from genome-wide association study(GWAS). Inverse variance weighting (IVW) was used as the main analysis method. Horizontal pleiotropy was identified by MR-Egger intercept test, MR pleiotropy residual sum and outlier (MR-PRESSO) test. The leave-one-out method was used as a sensitivity analysis. Results The IVW results indicated that there was a positive causal relationship between educational duration and BMD (OR = 1.012, 95%CI:1.003–1.022), physical activity(PA) (OR = 1.156, 95%CI:1.032–1.295), calcium consumption (OR = 1.004, 95%CI:1.002–1.005), and coffee intake (OR = 1.019, 95%CI:1.014–1.024). There was a negative association between whole body fat mass (OR = 0.950, 95%CI:0.939–0.961), time for vigorous PA (OR = 0.955, 95%CI:0.939–0.972), sunbath (OR = 0.987, 95%CI:0.986–0.989), salt consumption (OR = 0.965, 95%CI:0.959–0.971), fizzy drink intake (OR = 0.985, 95%CI:0.978–0.992), smoking (OR = 0.969, 95%CI:0.964–0.975), and falling risk (OR = 0.976, 95%CI:0.965–0.987). There was no significant association between educational duration and lean mass, time for light-to-moderate PA, milk intake, and alcohol intake. Horizontal pleiotropy was absent in this study. The results were robust under sensitivity analyses. Conclusion A longer educational duration was causally linked with increased BMD. No causal relationship had been found between educational duration and lean mass, time for light-to-moderate PA, milk intake, and alcohol consumption as risk factors for osteoporosis.